The Slovene version of a fast track to political equality - Antić Gaber, Milica (Teorija in praksa, 2017)
After the first multi-party election in the Slovene National Assembly the share of women MPs dropped dramatically (from 24 per cent in 1986 to 17.5 per cent in 1990) and did not substantially change during the following two decades. This led to a debate among feminist activists and scholars and left-oriented female politicians regarding the absence of effective measures to improve the situation. The first proposals to introduce gender quotas initially for internal party bodies and later for national elections were put forward by women in the centre and left-wing parties. The voluntary quotas adopted by these parties did not yield visible progress on the presence of women in important political bodies, as these parties' gatekeepers did not fully respect their own rules when composing candidate lists. It was only when legal quotas were introduced that significant changes occurred in the share of women at the highest levels of Slovene politics. In contrast to previous studies on gender quotas in Slovenia, this paper focuses on the importance of the legal and institutional mechanisms in the Slovene context that increased the number of women in politics and examines the political process that paved the way for greater gender equality by using data from elections and putting the data into a broader context. The authors conclude that without gender quotas imposed by legislation the percentage of women in the last parliamentary election in 2014 would not have increased to 37 per cent (the highest among CEE countries) but also identify some limitations to the effectiveness of quota regulations in the Slovene political and institutional context.
Keywords: delež žensk; Electoral system; Enakost moških in žensk; enakost spolov; Equality between men and women; gender equality; integracija načela enakosti spolov; Slovenia; Slovenija; strankarske kvote; Volilni sistem; Woman; Ženska; ženske kvote